Immediate Effect of Stretching Versus Strengthening Excercises on Blood Glucose Level in Chronic Diabetes Mellitus - Shweta M Mehta1 , Smita Patil2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background : Diabetes mellitus affects the muscles as muscle play notable role in the regulation of blood sugar level. The lack of glucose can lead to muscle cells atrophying and therefore loss of muscle mass. Stretching can increase cellular glucose uptake. Strengthening may improve strength , enlarged muscle mass and to improve insulin sensitivity and glycaemic control. Their paucity of literature on immediate effect of stretching versus strengthening exercises on blood glucose level in diabetes mellitus . Objective: To find out immediate effect of stretching on blood glucose level in diabetes mellitus individuals. To find out immediate effect of strengthening exercises on blood glucose level in diabetes mellitus individuals. To compare the immediate effectiveness of stretching and strengthening exercises on blood glucose level in diabetes mellitus individuals. Methodology: the study was conducted in Krishna hospital, in physiotherapy department. 44 subjects were selected with simple random sampling method. Chronic type 2 diabetes mellitus individuals were divided in to two groups. Group A (stretching) and group B (strengthening exercises)was given. The pre- and post –treatment postprandial Blood glucose values was measured by glucometer. Result: In conducted study, postprandial BGL showed statistically significant difference between pre and post treatment values in both group A and B. Conclusion: from the above conducted study it concludes that both stretching and strengthening exercises are effective in decreasing postprandial blood glucose level in type 2 diabetes mellitus, as there is no significant difference between both the groups . Strengthening exercises increased more flexibility in females than passive stretching and males were benefited with both stretching and strengthening exercises.